1994
DOI: 10.1111/j.1365-2044.1994.tb03422.x
|View full text |Cite
|
Sign up to set email alerts
|

The intensity of postoperative shivering is unrelated to axillary temperature

Abstract: SummaryThe relationship between axillary temperature and postoperative shivering was examined in 302 patients who entered one recovery room in the Derbyshire Royal Infirmary over a one-month period. No relationship was found between temperature and the occurrence of shivering, or between conscious level and the occurrence of shivering. Key wordsTemperature; body, regulation. Complications; shivering.Postoperative shivering is distressing for the patient and may impair the quality of recovery from anaesthesia b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(79 citation statements)
references
References 14 publications
2
75
0
2
Order By: Relevance
“…Therefore, it is reasonable to assume that, in the absence of a surgical procedure, hypothermia contributes for the development of tremors and that normothermia protects against it 12 . The study demonstrated that core temperature had only a slight influence on the development of tremors when compared with age (most important factor), and was compatible with the results of other studies that demonstrated that temperature has a weak predictive power for the development of tremors 36,37 . According to the analysis of multifactorial logistic regression, core temperature was not directly related with postoperative tremors in children, while the relative change of perioperative temperature was one of three independent predictors 38 .…”
Section: Physiopathologysupporting
confidence: 78%
See 3 more Smart Citations
“…Therefore, it is reasonable to assume that, in the absence of a surgical procedure, hypothermia contributes for the development of tremors and that normothermia protects against it 12 . The study demonstrated that core temperature had only a slight influence on the development of tremors when compared with age (most important factor), and was compatible with the results of other studies that demonstrated that temperature has a weak predictive power for the development of tremors 36,37 . According to the analysis of multifactorial logistic regression, core temperature was not directly related with postoperative tremors in children, while the relative change of perioperative temperature was one of three independent predictors 38 .…”
Section: Physiopathologysupporting
confidence: 78%
“…É, portanto, razoável presumir que a hipotermia contribui para tremor e que a normotermia é protetora, na ausência de intervenção cirúrgica 12 . O estudo demonstrou que a temperatura central teve apenas uma leve influência no desenvolvimento de tremores comparada com a idade (fator mais determinante) e foi compatível com resultados de outros estudos que mostraram que a temperatura tem um fraco poder preditivo para tremor 36,37 . De acordo com a análise de regressão logística multifatorial a temperatura central não foi diretamente relacionada com tremores pós-operatórios em crianças, enquanto a mudança relativa de temperatura perioperatória foi um dos três preditores independentes 38 .…”
Section: Fisiopatologiaunclassified
See 2 more Smart Citations
“…Exclusion criteria were as follows: History of severe cardiovascular complications, preoperative temperature >38˚C or <35˚C, any contraindications to regional anesthesia, ketamine allergy, preeclampsia, diabetes mellitus, significant peripartum hemorrhage or the existence of an absolute or relative contraindication for the application of the epidural technique, including neuromuscular disease, bleeding tendency or local skin infection in the lumbar region. A previous study (14) reported that intraoperative shivering is not associated with intraoperative temperature. The intraoperative room temperature and the temperature of the infusion liquid were controlled and, although the intraoperative temperature was monitored during the present study, it was not included as a detection index.…”
Section: Methodsmentioning
confidence: 99%